Kesiapan Guru dalam Menghadapi Tantangan Implementasi Kurikulum Merdeka: (Studi Kasus di Sekolah Menengah Atas) - Subhan Widiansyah; Serly Putri Hidayat; Sauqi Ichsan Kamil; Ida Dwi Lestari Br Purba; Usy Rahmawati; Feby Miftah Azmi Khairo (Lembaga Pengembangan Kinerja Dosen, 2025)
The curriculum is a fundamental component of the education system, designed to meet the evolving needs of society. In 2022, the Indonesian Ministry of Education, Culture, Research, and Technology introduced the Merdeka Curriculum as a strategic response to global challenges and the impacts of the COVID-19 pandemic. This study aims to analyze the implementation of the Merdeka Curriculum, identify the challenges encountered, and propose strategies to enhance its effectiveness. The research employs a literature review with a qualitative approach, underpinned by Structural Functional Theory to interpret the dynamics of curriculum implementation. The findings reveal significant disparities in teachers’ readiness to understand and implement the curriculum, influenced by factors such as training, resource availability, and institutional support. Major challenges include insufficient infrastructure, gaps in understanding, and resistance to pedagogical innovation. The study concludes that strengthening collaboration among teachers, schools, communities, and the government, combined with intensive training and infrastructure development, can optimize the curriculum’s potential in fostering globally competitive human resources. It is recommended that all stakeholders actively engage in cross-sector collaboration to ensure the sustainable implementation of the Merdeka Curriculum.